Harcourt science - Marjorie Slavick Frank (Orlando, Florida : Harcourt School Publishers, 2000)
When scientist try to find an answer to a question or do an experiment, they use thinking tools called process skills. You use many of the process skills whenever you think, listen, read and write.
UnitA. Processes of Living Things -- UnitB. Systems and Interactions in Nature -- UnitC. Processes that Change the Earth -- UnitD. The Solar System and Beyond -- UnitE. Building Blocks of Matter -- UnitF. Energy and Motion .
Title from teacher's ed Teacher resource title: Activity book Trade books are part of Science instant readers series Equipment kit: Demonstration package may be used with this title "Life, Earth, and Physical Science; Units A-F"--Cover teacher's ed
Includes index.
Keywords: SCIENCE